Intervenciones de enfermería en pacientes de cirugía reconstructiva de lesiones térmicas: revisión sistemática - Reyes Barrera, Gabriela Analía (2025)
Introduction: The care provided by the nursing professional must be comprehensive, personalized, humane and attentive to the needs of each individual. Thermal injuries have a high incidence in the current population. Objective: To update nursing interventions in patients undergoing reconstructive surgery for thermal injuries, in order to improve clinical outcomes and quality of life of patients. Methodology: This research is descriptive, cross - sectional and explanatory in design. In addition, the inductive and synthetic analytical method was used, where the Preferred Reporting Items for Systematic reviews and MetaAnalyses (PRISMA) methodology was implemented, under bioethical principles of article review. Outcomes: Nursing care addresses needs such as feeding, rest, infection prevention and emotional care. Interventions such as early debridement and autografting are essential in the management of partial thickness and deep burns. A multidisciplinary approach to infection control improves clinical outcomes and emotional support for the patient and family, using strategies to ensure comfort, effective communication and pain management. The review of scientific evidence on thermal injuries highlights structured care with standardized care plans and nursing staff training to improve care and clinical outcomes. Conclusion: The severity of thermal injuries offers the opportunity to provide specific and highly technical nursing care for recovery and quality of life of such patients.